MEDIA LITERACY IN BRAZILIAN PUBLIC SCHOOLS: A SYSTEMATIC REVIEW OF SCIENTIFIC PRODUCTION (2015–2025) (REMUNOM, 2026)
The technological transformations of recent decades have brought about significant changes in communication, production, and circulation of knowledge in contemporary society. The expansion of the internet, social networks, and digital platforms has consolidated a scenario marked by the intensification of information flows and the constant presence of Information and Communication Technologies (ICTs) in daily social life. In this context, digital culture has come to directly influence different dimensions of social life, including educational processes, requiring the development of skills related to the critical and reflective use of media and digital technologies. Given this scenario, media literacy emerges as a relevant educational approach for the formation of citizens capable of understanding, analyzing, and critically interpreting the information circulating in digital environments. By stimulating critical thinking, intellectual autonomy, and civic participation, this educational perspective contributes to preparing students to deal with the challenges of contemporary society, marked by informational abundance, the circulation of misinformation, and the growing influence of digital platforms in mediating access to knowledge. In this context, the present study aimed to analyze Brazilian scientific production published between 2015 and 2025 on media literacy in the school environment, focusing on the context of public schools, seeking to identify theoretical trends, methodological approaches, and challenges related to the integration of digital culture into pedagogical practices. To this end, a systematic literature review was conducted, searching academic databases such as SciELO, Google Scholar, and the CAPES Periodicals Portal, using descriptors related to the investigated theme. The selected studies were analyzed using content analysis techniques, allowing the identification of recurring thematic categories. The results indicate advances in educational policies focused on digital culture, but also highlight challenges related to technological infrastructure, access to technologies, and teacher training for the pedagogical use of media.